Access to Pyrrole Derivatives in Water with the Assistance of Methylated Cyclodextrins. Issue 20 (28th May 2014) - Menuel, Stéphane; Rousseau, Jolanta; Rousseau, Cyril; Vaičiūnaite, Edita; Dodonova, Jelena; Tumkevičius, Sigitas; Monflier, Eric
Abstract: A new and efficient catalytic protocol with which to synthesize N ‐substituted pyrrole derivatives from amines and 1, 4‐diketones by Paal–Knorr condensation in aqueous medium has been developed by using partially methylated β‐cyclodextrins (RAME‐β‐CD). The modified cyclodextrins were used as mass transfer agents without catalyst for reactive ketones and with nitrophenol as catalyst for more hindered ketones. Abstract : Methylated β‐cyclodextrins catalyze the synthesis of N‐substituted pyrroles in biphasic media from amines and 1, 4‐diketones.